Incidence, Risk Factors and Management of Symptomatic Lymphoceles after Radical Retropubic Prostatectomy. Issue 6 (November 2017) - Thomas, Christian; van de Plas, Jeoren; Tsaur, Igor; Neisius, Andreas; Bartsch, Georg; Frees, Sebastian; Borgmann, Hendrik; Jäger, Wolfgang; Brandt, Maximilian Peter; Haferkamp, Axel; Rubenwolf, Peter
Abstract : Introduction: : We investigated the incidence, clinical course and risk factors for symptomatic lymphoceles after radical retropubic prostatectomy with pelvic lymph node dissection. Moreover, we explored parameters for the failure of percutaneous lymphocele drainage. Methods: : The incidence of symptomatic lymphoceles in patients with prostate cancer who underwent radical retropubic prostatectomy with pelvic lymph node dissection in our department between 2008 and 2013 was investigated retrospectively. The occurrence of lymphoceles was correlated with several clinical and histopathological parameters. In addition, logistic regression analysis was performed to assess the value of independent variables with regard to the development of symptomatic lymphoceles and failure of percutaneous drainage. Results: : A total of 599 consecutive patients treated with radical retropubic prostatectomy with pelvic lymph node dissection were included in the study, of whom symptomatic lymphocele had developed in 5%. Median time to diagnosis of symptomatic lymphocele was 22.5 days. Median time of percutaneous drainage was 16 days. Overall 43% of patients required surgical unroofing. On multivariate analysis age greater than 67 years (OR 3.27, p=0.005) and removal of more than 10 lymph nodes (OR 2.57, p=0.018) were independent predictors for the development of symptomatic lymphoceles. A significantly increased risk of percutaneous drainage failure was observed in patients who had a body mass index greater than 27 kg/m 2 (OR 7.0, p=0.03), followed by a trend for those with a drainage volume of more than 375 ml 24 hours after puncture (OR 3.89, p=0.12). Conclusions: : Symptomatic lymphocele will develop in 1 of 20 patients after radical retropubic prostatectomy with pelvic lymph node dissection. The number of lymph nodes removed constitutes an independent risk factor. Percutaneous drainage failure is associated with high body mass index and high drainage volume within the first 24 hours after puncture.